2015
DOI: 10.1186/s40337-015-0064-0
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity, spirituality in relation to disordered eating and body image concerns: A systematic review

Abstract: ObjectiveThis systematic review aims to critically examine the existing literature that has reported on the links between aspects of religiosity, spirituality and disordered eating, psychopathology and body image concerns.MethodA systematic search of online databases (PsycINFO, Medline, Embase and Web of Science) was conducted in December 2014. A search protocol was designed to identify relevant articles that quantitatively explored the relationship between various aspects of religiosity and/or spirituality an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
3
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 50 publications
1
46
3
4
Order By: Relevance
“…The result is at odds with current literature reporting a positive relationship between religious observance and lower levels of DEP (Gluck & Geliebter, 2002;Latzer, Tzischinsky, & Gefen, 2007;Mahoney et al, 2005). Our finding may be explained by the recruitment of a religiously and spiritually diverse sample of secular university students compared to recruitment from private American universities reporting high percentages of Christian (53-99%) and/or Jewish participants (Akrawi et al, 2015). While Judeo-Christian practices, including prayer and the reading of religious text, have been shown to improve body image concerns (Boyatzis, Kline, & Backof, 2007;Kim, 2006), only 34.5% of participants in the current study identified with a traditional Judeo-Christian religious affiliation.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…The result is at odds with current literature reporting a positive relationship between religious observance and lower levels of DEP (Gluck & Geliebter, 2002;Latzer, Tzischinsky, & Gefen, 2007;Mahoney et al, 2005). Our finding may be explained by the recruitment of a religiously and spiritually diverse sample of secular university students compared to recruitment from private American universities reporting high percentages of Christian (53-99%) and/or Jewish participants (Akrawi et al, 2015). While Judeo-Christian practices, including prayer and the reading of religious text, have been shown to improve body image concerns (Boyatzis, Kline, & Backof, 2007;Kim, 2006), only 34.5% of participants in the current study identified with a traditional Judeo-Christian religious affiliation.…”
Section: Discussioncontrasting
confidence: 56%
“…However, only existential beliefs remained a significant predictor of lower levels of DEP throughout hierarchical regression analyses, even amongst participants who associated with a religious affiliation. This contrasts with evidence reported in a recent systematic review (Akrawi et al, 2015) which summarised studies showing evidence for associations between religious beliefs and lower levels of DEP in traditional religious samples. According to the authors of the SRPB scale (Skevington et al, 2013), religious beliefs reflect the extent to which a person's faith and a connection to a transcendental being helps an individual get through hard times and live a better life.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Another randomized, control group design study to evaluate the effectiveness of a spiritual group intervention for inpatient eating disorders compared the effectiveness of a Spirituality group with Cognitive and Emotional Support groups [28]. On weekly outcome measures, patients in the Spirituality group improved significantly more quickly during the first four weeks of treatment, thus suggesting preliminary evidence that promoting spiritual growth and well-being of patients with eating disorders patients could contribute to a reduction in their symptoms [28]. In another systematic study that examined the effects of religiosity, spirituality on eating disorders and body image concerns recommended pursuing further investigation into the protective benefits of religiosity and spirituality in the progression of eating disorders [29].…”
Section: Discussionmentioning
confidence: 99%
“…To determine the efficacy of these groups; a Cochrane Database Systematic Review was conducted and concluded with mixed results about their effectiveness [27]. Another randomized, control group design study to evaluate the effectiveness of a spiritual group intervention for inpatient eating disorders compared the effectiveness of a Spirituality group with Cognitive and Emotional Support groups [28]. On weekly outcome measures, patients in the Spirituality group improved significantly more quickly during the first four weeks of treatment, thus suggesting preliminary evidence that promoting spiritual growth and well-being of patients with eating disorders patients could contribute to a reduction in their symptoms [28].…”
Section: Discussionmentioning
confidence: 99%